The readiness of Takaful operators to adopt Waqf (endowment) as additional feature in Takaful policy / Amirul Afif Muhamat... [et al.] - Muhamat, Amirul Afif; Ahmad, Siti Zubaidah; Roslan, Azreen; Abdul Karim, Norzitah; Ali Azizan, Norfaridah (Universiti Teknologi MARA, Negeri Sembilan, 2019)
This paper aims to explore the readiness of takaful operators to integrate waqfas part of their product feature by assessing on the components of as proposed in the New Product Development Model: marketing supports; formalized development process and top management supports. Questionnaire was employed in this survey and takafuloperators’ employees who involved in product development were selected such as actuaries, business development managers and their executives. Unexpectedly, several takafuloperators withdrew from participating in the survey (it was last minute) –which is limitation in this study. Accordingly, it caused the use of non-parametric tests in this study since the data is not normally distributed. Spearman rank correlation shows that formalized development process is the significant factor that influenced the readiness of the takaful operators to integrate waqf in their products. However, the other two independent variables which are marketing supports and top management supports depicted insignificant result. Nevertheless, the findings were still able to provide insights on the integration of waqfby takafuloperators as their latest products’ feature.